TYPES OF POSSESSIVE PRONOUNS IN LAMAHOLOT LANGUAGE OF LAMALERA DIALECT - Veronika Genua; Yosef Demon (Denpasar Institute, 2020)
All languages have possessive or genitive form. However, possessive in every language differs from one language to another. Lamaholot Language of Lamalera Dialect has four forms of possessive which are often used in communicating. The use of these four forms depends on the speaker and the situation of speech. Morfonological change Phonological and morphological change occur Morphonological changes occur as a result of morphological processes. This morphonological phenomenon occurs in all forms of possessive both pronomina possessive and adjective possessive. Semantically the possessive meaning of the pronoun states ownership and intensity. Data were collected by observation. The analysis is performed using an inductive-deductive or deductive-inductive reasoning